PENYULUHAN PENTINGNYA PENINGKATAN VO2MAX GUNA MENINGKATKAN KONDISI FISIK PEMAIN PADA ATLET BOLA BASKET SMA AL AZHAR SYFA BUDI PEKANBARU II - Oki Candra; Ahmad Rahmadani; Putri Wahyuni; Anggara Oktaviandi; Rizky Pratama Khairullah (Bajang Institute, 2023)
Basketball is a high-intensity sport with a game time of 4x10 minutes. For that a basketball game requires extraordinary physical condition. One of the main physical conditions in this game is the Vo2max or cardiovascular endurance, where a basketball player must be able to last as long as possible to keep his ring so as not to fail and how the player survives to score many numbers. The problem in the field is that there are still many athletes who are exhausted during the competition, which leads to a decrease in athlete's performance and the static that has been prepared cannot be applied to the maximum. As for the solutions offered by the researchers: 1) We organized a series of training sessions for basketball players and coaches at Al Azhar Sifa Budi Pekanbaru II High School. The training covers the understanding of VO2max, its enhancement methods, and the importance of physical condition in basketball, 2) After that, Physical Training: We also involve participants in physical training sessions designed to increase VO2 max. This includes aerobic exercises, such as running and strength training to improve overall physical condition. 3) Furthermore, the use of pre- and post-event questionnaires to measure knowledge changes is an effective evaluation method. Results of Dedication: 1) Increased understanding: Through understanding, participants, including basketball players, have gained a better understanding of the role of VO2max in athletic performance, 2) Increase in Practical Knowledge: Participants have acquired practical knowledge about methods of exercise that can help increase their VO2Max, 3) Positive Impact on Physical Condition: Over time, the understanding and physical training given has had a positive impact on the physical condition of basketball player, 4) Awareness of Health: In addition to the benefits of performance, participants are also more aware of the importance of physical health and fitness specifically vo2max